An open, integrated modular format: For flexible and intelligible architecture, engineering and construction design and production. (March 2021) - Doe, Robert Melvin
The architecture, engineering and construction sector is fragmented, and its computer-aided design systems suffer data loss and errors in workflow between design and realisation. An open source, integrated, modular format is proposed to address the technological nature of these problems. Accordingly, this research updates the notion of the modular format as a more flexible and intelligible computational design method by leveraging knowledge from the computer science and manufacturing sectors where the design and realisation process is intentional and explicit. The research design of this article comprises a theoretical approach combined with an empirical case study. Principles of modularity are extracted from the computer science and manufacturing sectors to assist with a better definition of architecture, engineering and construction computer-aided design processes that use materials and resources more efficiently and sustainably. The methodology of the modular format contributes to the emerging concept of a building lifecycle management system for the architecture, engineering and construction sector.